Obstructive sleep apnea and cardiovascular diseases - Kloch-Badełek, Małgorzata; Czarnecka, Danuta; Wiliński, Jerzy; Kusiak, Aleksander (Przewodnik Lekarza/Guide for GPs, 2008)
Obstructive sleep apnea is nowadays frequently diagnosed. Research data indicate a connection between sleep-related breathing disturbances and prevalence of hypertension, development and prognosis of coronary artery disease, pulmonary hypertension, heart rhythm abnormalities and in patients after stroke. These reports should be seriously considered as cardiovascular diseases are the leading cause of global mortality.